The Novel Agrotis ipsilon Nora Virus Confers Deleterious Effects to the Fitness of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Li, Tong; Guan, Ruobing; Wu, Yuqing; Chen, Su; Yuan, Guohui; Miao, Xuexia; Li, Haichao (Frontiers in Microbiology, 2021)
In the present study, we identified a novel, positive-sense single-stranded RNA virus in the Chinese black cutworm, Agrotis ipsilon. It has a genome length of 11,312 nucleotides, excluding the poly(A) tails, and contains five open reading frames. The ORF2 encodes the conserved domains of RNA helicase and RNA-dependent RNA polymerase, while ORF4 and 5 encode three viral proteins. Herein, the A. ipsilon virus was clustered with a Helicoverpa armigera Nora virus and was thus provisionally named “Agrotis ipsilon Nora virus” (AINV). AINV was successfully transmitted into a novel host, Spodoptera frugiperda, through injection, causing a stable infection. This found the possibility of horizontal AINV transmission among moths belonging to the same taxonomic family. Nonetheless, AINV infection was deleterious to S. frugiperda and mainly mediated by antiviral and amino acid metabolism-related pathways. Furthermore, the infection significantly increased the S. frugiperda larval period but significantly reduced its moth eclosion rate. It suggests that AINV is probably to be a parasitic virus of S. frugiperda.